Stochastic inflation with quantum and thermal noise - Z. Haba (European Physical Journal C: Particles and Fields, 2018)
Abstract We add a thermal noise to Starobinsky equation of slow roll inflation. We calculate the number of e-folds of the stochastic system. The power spectrum and the spectral index are evaluated from the fluctuations of the e-folds using an expansion in the quantum and thermal noise terms.